Managing Transnational UNESCO World Heritage sites in Africa
XVIII, 202 p. 1 illus.
Keywords: This open access book focuses on the management of transboundary UNESCO World Heritage sites in the Africa region. It highlights the region as a model of best practices on cross-border collaboration in view of enforcing the conservation of the site, engaging with local communities, and fighting against (in some cases) extremist groups inhabiting these sites. It also addresses the role of the World Heritage Convention in promoting transboundary cooperation and offers both an analysis and a list of priorities for improving the effective management of transboundary properties in sub-Saharan Africa defined. This book presents chapters from experts, site managers, technical and financial partners, academics, and representatives of the private sector from 20 African countries and 15 institutions involved in African heritage management. It provides an opportunity to share current and planned initiatives at the transboundary sites inscribed on the UNESCO World Heritage List, including the Maloti-Drakensberg Park (South Africa, Lesotho), W-Arly-Pendjari Complex (Benin, Burkina Faso, Niger), Sangha Trinational (Cameroon, Congo, Central African Republic), and Mosi-oa-Tunya / Victoria Falls (Zambia, Zimbabwe). The publication further discusses African sites that could eventually be proposed for extension or nomination to the UNESCO World Heritage List in collaboration with the local and indigenous communities. This book is suitable for heritage specialists and readers interested in cross-border collaborations.